Pengembangan Media Pembelajaran Berbasis Android pada Materi Gerak Parabola Untuk Siswa SMA - Marhadini, Satria Adhi Kusuma; Akhlis, Isa; Sumpono, Imam (UPEJ Unnes Physics Education Journal, 2017)
The development of science and technology encourages various reform efforts in the learning process. Meanwhile, teachers are required to be able to utilize information and communication technology for self-development. Android is one of the most popular operating systems today. The purpose of this research is to make android instructional media that has the appropriate characteristics so that it is suitable for high school students. The development of this medium follows the Borg and Gall groove that has been simplified by the Center for Policy Research and Innovation consisting of 4 stages of needs analysis, initial design, validation and revision, small-scale and revised trials. In the development study, the learning medium has been validated by an expert validator with 77.53% results or is eligible to use. Trial program conducted by students at 2nd Muhammadiyah Senior High School at Magelang city with a result of 68.82% or eligible to use. Research data collection method used is observations, questionnaires and documentation. Based on data analysis then in this study can be concluded android learning media on parabolic motion material can be used as alternative learning resources with offline characteristics, practice questions and android operating system specifications minimum 5.0.